Government-Sponsored Training Programs and Sustainability of Small Businesses in Lagos State, Nigeria - Maxwell, Ochade (NIU Journal of Social Sciences, 2025)
Small and medium enterprises (SMEs) are key drivers of economic growth, employment and innovation, particularly in developing areas like Nigeria. In the commercial nerve centre of Nigeria, Lagos State, SMEs generate income for many and form a substantial share of the Gross Domestic Product (GDP). Realising that small enterprises have significant roles to play, the Nigerian governments have embarked on several interventions in terms of capacity building and these they do through training in management techniques, technology of production and management of operations. Despite the intuitive appeal and the high prevalence of these programs, their effectiveness at the long-run survival of small businesses is not clear. The government supported training programmes and sustainability of small businesses in Lagos State, Nigeria This study examines the nexus between government sponsored training programmes and sustainable small businesses in Lagos State. Utilising a correlation research design as a survey approach, 174 small business owners in Lagos provided responses to structured questionnaires. The analysis shows a positive but statistically non-significant (p > 0.05, r = 0.20) relationship between government-sponsored training participation and business sustainability. These results indicate that current training interventions may not be successful enough in embedding business growth in Lagos. The research also suggests that training programs should be customised according to industry demands, disseminated through digital channels in order to reach a wider audience and be accompanied by ongoing mentoring, financial and market support aimed at maximising impact. Enhancement of the relevance and support functions of these programs would help to enhance the resilience and long-term survival of small businesses in Lagos State. Keywords: Small Businesses, Government Training, Business Sustainability, Lagos State, Capacity Building.